A density functional theory-based investigation of adhesion of poly(butylene terephthalate) on aluminum - David, Melanie Y. (Animo Repository, 2006)
We investigate the adhesion of PBT on aluminum using density functional theory-based calculations. The geometric structure of the PBT monomer is first relaxed then an aluminum atom is connected to the monomer in different orientations. We calculate their total energies and determine the orientation that gives the strongest binding between the monomer and the aluminum atom. Binding is strongest when the Al connects linearly with the carbonyl oxygen in the ester group. We present binding mechanisms and total energy relationships for the different orientations.